Teacher-students interactions and Students’ attitude at international science faculty classes: in the context of biology and chemistry departments - Ratmanida, Ratmanida; Ayudhia, Honesty Yonanda; Adzanil, Fuad Nabil; Putri, Meutia Herza (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
In the context of globalization of education, where students often come from diverse cultural and academic backgrounds, interactions between teachers and students play a key role in effective learning experiences. This research emerged from awareness of the need to understand how interactions between teachers and students occur in international classrooms, particularly in biology and chemistry departments. This research aims to analyze differences in student interactions in international classes based on science faculties. This research is comparative research obtained through random sampling. The sample for this research was 88 students who were enrolled in the international class program at the science faculty. Data was collected using an in-class interaction instrument with 29 items. The analysis technique uses descriptive and independent sample t-tests. These findings indicate that there are significant differences in the level of interaction between students majoring in biology and chemistry in international classes. Apart from that, classroom interaction also provides opportunities for collaboration between students so that they can increase their self-confidence in their learning abilities. Building strong relationships among students also contributes to increasing positive attitudes towards learning through motivation and engagement.